Carcinomatous Lymphangitis in adolescence: A purpose of a case (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
Carcinomatous lymphangitis is a rare entity, with high mortality; characterized by tumor lymphatic colonization secondary to a primary neoplasm. We present a 19-year-old patient with 5 weeks of evolution characterized by productive cough, slightly hemoptotic, nausea, vomiting and chest pain. Chest tomography was requested and showed signs suggestive of the pathology. Bronchoscopy was performed with biopsy revealing squamoid cell carcinoma and lymph node biopsy of lymphoid tissue with metastasis of carcinoma. It is very important to evaluate this pathology in adolescents, since its infrequency may contribute to its diagnosis at a late stage.